2008
DOI: 10.1002/jsfa.3431
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of DGAT1 associated with intramuscular fat‐mediated tenderness in sheep

Abstract: BACKGROUND: Polymorphism of acyl coenzyme A: diacylglycerol acyltransferase 1 (DGAT1) affects the fat content of milk and meat in cattle. To investigate the effects of DGAT1 on sheep meat quality traits, the cDNA of DGAT1 was cloned. The association between single nucleotide polymorphisms of the DGAT1 gene and sheep meat quality traits was assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
3
20
0
3
Order By: Relevance
“…It has been previously reported in other studies at various sheep breeds by Xu et al (2008) These studies were performed on various individuals and several mutations were found besides the one revealed in our study in exon 17. These author concluded also that there is no signi icant association with the milk fat content.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…It has been previously reported in other studies at various sheep breeds by Xu et al (2008) These studies were performed on various individuals and several mutations were found besides the one revealed in our study in exon 17. These author concluded also that there is no signi icant association with the milk fat content.…”
Section: Resultssupporting
confidence: 80%
“…These author concluded also that there is no signi icant association with the milk fat content. However, Xu et al (2008) has revealed a signi icant association of this polymorphism with the IMF content, muscle marbling score and meat tenderness. The authors have concluded that the T allele, which was found in a lesser frequency in our study, had a positive effect on sheep meat quality traits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also include the thyroglobulin (TG) gene in cattle (Barendse, 2002), the diacylglycerol acyltransferase 1 or 2 (DGAT1; DGAT2) genes in cattle (Thaller et al, 2003), pigs (Nonneman and Rohrer, 2002), chicken (Bourneuf et al, 2006) and sheep (Xu et al, 2009), and the splicing factor serine-arginine-rich protein (SFRS18) gene in pigs (Wang et al, 2009b). However, the results are often inconsistent.…”
Section: Genetic Markersmentioning
confidence: 99%
“…These genes are involved in muscle development, growth (Nonneman and Koohmaraie, 1999) as well as in eating quality (tenderness) of the mutton (Byun et al 2009). The DGAT1 and FABP3 are involved in fatty acid metabolism and associated with milk fat content and marbling (Scata et al 2009;Xu et al 2009). It is imperative that knowledge be acquired of the available Indian sheep populations which are as yet untouched reservoirs of potential genes defining mutton quality.…”
Section: Introductionmentioning
confidence: 99%